2012
DOI: 10.1108/02637471211213398
|View full text |Cite
|
Sign up to set email alerts
|

Use of blended learning to enhance the student learning experience and engagement in property education

Abstract: Purpose -This paper aims to report the detailed findings of a Centre for Education in the Built Environment (CEBE) funded study into good practice in the use of blended learning in property education. "Blended learning" is a combination of face-to-face learning experiences and online learning experiences which aim to complement each other in order to support and enhance student learning. The aim of this paper is to examine the benefits that blended learning provides to students' learning experience and engagem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 15 publications
5
69
0
8
Order By: Relevance
“…Meta-analyses also clearly demonstrate the effectiveness of blended learning on student achievement when compared to online and face-to-face learning (Batdı, 2014;Çırak-Kurt, Yıldırım, & Cücük, 2017;Means, Toyama, Murphy, Bakia, & Jones, 2009). Besides, there are studies addressing blended learning from different perspectives (Geçer, 2013;Kocaman-Karoğlu, Kiraz, & Özden, 2014;López-Pérez et al, 2011;Poon, 2012) and those investigating the effects of blended learning environments enriched via various methods such as gamification and 5E (Kurt, 2012;Meşe, 2016;Yıldırım, 2016). It was also concluded that blended learning research conducted in Turkey were mainly postgraduate dissertations examining the effects of the blended learning on certain variables such as motivation (Aygün, 2011;Cabi, 2009), attitude (Çiftçi & Dönmez 2015), anxiety reduction (Horzum & Çakır Balta, 2008), permanence (Aksoğan, 2011), self-regulatory learning skills (Ateş Çobanoğlu, 2013;Güler, 2013), professional know-how (Kaya 2014;Sungur, 2014), critical thinking and creative skills (Umar, 2014) and self-efficacy (Demirer, 2009) and the majority of those revealed positive variations on the aforementioned variables.…”
mentioning
confidence: 99%
“…Meta-analyses also clearly demonstrate the effectiveness of blended learning on student achievement when compared to online and face-to-face learning (Batdı, 2014;Çırak-Kurt, Yıldırım, & Cücük, 2017;Means, Toyama, Murphy, Bakia, & Jones, 2009). Besides, there are studies addressing blended learning from different perspectives (Geçer, 2013;Kocaman-Karoğlu, Kiraz, & Özden, 2014;López-Pérez et al, 2011;Poon, 2012) and those investigating the effects of blended learning environments enriched via various methods such as gamification and 5E (Kurt, 2012;Meşe, 2016;Yıldırım, 2016). It was also concluded that blended learning research conducted in Turkey were mainly postgraduate dissertations examining the effects of the blended learning on certain variables such as motivation (Aygün, 2011;Cabi, 2009), attitude (Çiftçi & Dönmez 2015), anxiety reduction (Horzum & Çakır Balta, 2008), permanence (Aksoğan, 2011), self-regulatory learning skills (Ateş Çobanoğlu, 2013;Güler, 2013), professional know-how (Kaya 2014;Sungur, 2014), critical thinking and creative skills (Umar, 2014) and self-efficacy (Demirer, 2009) and the majority of those revealed positive variations on the aforementioned variables.…”
mentioning
confidence: 99%
“…Alan yazında harmanlanmış öğrenmeye dair pek çok tanımlama ile karşılaşılmakta (Driscoll, 2002;Garrison ve Kanuka, 2004;Jonas ve Burns, 2010;Osguthorpe ve Graham, 2003;Williams vd., 2008;Yen ve Lee, 2011) ancak tam olarak sınırları belli bir tanımın henüz belirlenmediği, her çalışmanın kendine özgü çerçevesinin olduğu ve mevcut tanımların ortak özellikler taşıdığı yapılan araştırmalarda da belirtilmektedir (Aygün, 2011;Bliuc vd., 2007;Osgerby, 2013;Picciano vd., 2013;Poon 2012;Sharpe vd., 2006). Bir diğer deyişle alan yazında harmanlanmış öğrenme üzerine ilgili teknolojiler ve uygulama çeşitliliğini yansıtacak kadar çok tanım yer almaktadır.…”
Section: Introductionunclassified
“…Ayrıca harmanlanmış öğrenmeyi farklı yönleri ile ele alan (Geçer, 2013;Kocaman-Karoğlu vd., 2014;López-Pérez vd., 2011;Nor ve Kasim, 2015;Poon, 2012) ve harmanlanmış öğrenmenin çeşitli değişkenler üzerindeki etkisini inceleyen araştırmalara (Ateş-Çobanoğlu, 2013;Kirişçioğlu, 2009;Yen ve Lee, 2011;Kashefi vd., 2012;Sophonhiranraka vd., 2014;Motteram, 2006) rastlanmaktadır. Örneğin Yen ve Lee (2011) ile Sophonhiranraka vd.…”
Section: Introductionunclassified
“…an online approach) (Bersin, 2004, cited in Onguko et al, 2013, is gathering in popularity for professionals, as it enables a greater degree of flexibility for engagement. Within the built environment sector, literature suggests that blended learning is used widely and is able to provide "simulated learning experiences" to its participants (Poon, 2012;Poon, 2013). Although care must be taken; there are certain topics for which blended learning would not be suitable; and for certain trades, there is no substitution for faceto-face and practical learning approaches.…”
Section: Introductionmentioning
confidence: 99%